Inhibition of anti-inflammatory cytokines, IL-10 and TGF-β, in Leishmania major infected macrophage by miRNAs: A new therapeutic modality against leishmaniasis. (April 2021) - Hamidi, Faezeh; Mohammadi-Yeganeh, Samira; Haji Molla Hoseini, Mostafa; Seyyed Tabaei, Seyyed Javad; Taghipour, Niloofar; Lasjerdi, Zohreh; Gholamrezaei, Mostafa; Haghighi, Ali
Abstract: Leishmania major (L. major) applies several mechanisms to escape the immune system. Interleukin-10 (IL-10) and Transforming Growth Factor (TGF-β) downregulate nitric oxide synthase (iNOS) leading to the survival of Leishmania within macrophages. The miRNAs are known as the modulators of the immune system. The present study was conducted to assess the effect of synthetic miR-340 mimic on cytokines (IL-10 and TGF-β1) involved in L. major infected macrophages. The miRNAs targeting of IL-10 and TGF-β1 was predicted using bioinformatic tools. Relative expression of predicted miRNA, IL-10, and TGF-β1 was measured by RT-qPCR before and after synthetic miRNA mimic transfection. Concentration of IL-10 and TGF-β was measured in posttreatment condition using ELISA method. Also, infectivity was assessed by Giemsa staining. mmu-miR-340 received the highest score for targeting cytokines. The expression of miR-340 was downregulated in L. major infected macrophages. By contrast, expression of IL-10 and TGF-β1 was upregulated in infected macrophages. After miRNA transfection, TGF-β1 and IL-10 were both downregulated and interestingly, the combination of miR-340 and miR-27a had a stronger effect on the downregulation of target genes. This research revealed that transfection of infected macrophages with miR-340 alone or in combination with miR-27a mimic can reduce macrophage infectivity and might be introduced as a novel therapeutic agent for cutaneous leishmaniasis. Highlights: Evaluation of the effect of miR-340 mimic on IL-10 and TGF-β1 in L. major infected macrophages Downregulation of miR-340 was observed in L. major infected macrophages Upregulation of IL-10 and TGF-β1 genes was detected in L. major infected macrophages After miRNA mimic transfection, the combination of miR-340 and miR-27a had more effect on IL-10 and TGF-β1 downregulation